Distinct expression of the neurotoxic microRNA family let-7 in the cerebrospinal fluid of patients with Alzheimer's disease. - Katja Derkow; Rosa Rössling; Carola Schipke; Christina Krüger; Jakob Bauer; Michael Fähling; Andrea Stroux; Eckart Schott; Klemens Ruprecht; Oliver Peters; Seija Lehnardt (PLoS ONE)
MicroRNAs (miRNAs) are non-coding RNAs originally involved in RNA silencing and post-transcriptional regulation of gene expression. We have shown in previous work that the miRNA let-7b can act as a signalling molecule for Toll-like receptor 7, thereby initiating innate immune pathways and apoptosis in the central nervous system. Here, we investigated whether different members of the miRNA family let-7, abundantly expressed in the brain, are released into the human cerebrospinal fluid (CSF) and whether quantitative differences in let-7 copies exist in neurodegenerative diseases. RNA isolated from CSF of patients with Alzheimer´s disease (AD) and from control patients with frontotemporal lobe dementia (FTLD), major depressive episode (MDE) without clinical or neurobiological signs of AD, and healthy individuals, was reverse transcribed with primers against nine let-7 family members, and miRNAs were quantified and analyzed comparatively by quantitative PCR. let-7 miRNAs were present in CSF from patients with AD, FTLD, MDE, and healthy controls. However, the amount of individual let-7 miRNAs in the CSF varied substantially. CSF from AD patients contained higher amounts of let-7b and let-7e compared to healthy controls, while no differences were observed regarding the other let-7 miRNAs. No increase in let-7b and let-7e was detected in CSF from FTLD patients, while in CSF from MDE patients, let-7b and let-7e copy levels were elevated. In CSF from AD patients, let-7b and let-7e were associated with extracellular vesicles. let-7 family members present in the CSF mediated neurotoxicity in vitro, albeit to a variable extent. Taken together, neurotoxic let-7 miRNAs are differentially and specifically released in AD, but also in MDE patients. Thus, these miRNAs may mirror common neuropathological paths and by this serve to unscramble mechanisms of different neurodegenerative diseases.